KALYANAKARAKAM – A GEM OF AYURVEDA - D N, *Patil; Babu N, Darshan; Baragi, Umapati C.; Gouda H, Pampanna; N J, Patil (AYUSHDHARA, 2015)
Background: The origin of Ayurveda is lost in mysteries of time; since the earliest human civilization, man has sought ways to heal himself. Human civilization progressed, bringing in sophisticated thought & research behind medicine. It is believed that a system of medicine was prevalent in India in pre Vedic times. The Vedas are the earliest written records of the wisdom & insights of Indian seekers & scholars. Medicine is an ever changing science. Literary research is must in today’s perspective to get the hidden & unexplored knowledge. On this regard many Acharya’s contributed to ancient science i.e. Ayurveda. Jain seers have written several texts in Sanskrit on Ayurveda they are similar in content & finding to Vedic text. One among them is Kalyanakarakam, was composed by Acarya Ugraditya, a Jain monk who is believed to have lived in the 9th century of the Common Era. This text comprises of 667 Sanskrit hemistich divided into 25 chapters and one special section on predicting death. The chapters cover all aspects of Ayurveda with great depth and thoroughness. Aims & Objective: 1) To compile the literature bearing Svastha Rakshana i.e. preventive aspects in the form of Dinacharya (daily regimen), Rutu-charya (seasonal regimen) etc. &some other concepts like knowledge about Prakruti (nature) Desha (region), Kala (time), important anatomical structures, and regimens for pregnant women etc. Materials & Methods: Study aims to review the preventive aspects which are mentioned in Kalyanakarakam. Conclusion: Inculcating all the concepts which elucidates the concept of prevention is much essential in today’s perspective.